Penyaluran Dana ZIS dan Tingkat Inflasi Berpengaruh Terhadap Pertumbuhan Ekonomi Indonesia Periode 2011-2015 - Rachmasari Anggraini; Tika Widiastuti (Jurnal Ekonomi Syariah Teori dan Terapan, 2017)
This study aims to analyze the influence of ZIS fund's and inflation towards the economic growth in Indonesia during 2011-2015. The research method is quantitative method with multiple linear regression technique. The data used is the collected secondary data of remittances of ZIS from BAZNAS (national amil zakat agency) and inflation rate of BI (Bank of Indonesia) in Indonesia during 2011-2015 that includes monthly data all over Indonesia. The results of the research indicates that the funds of ZIS (X1) affects positively and significantly towards Indonesia's economic growth and inflation (X2) do not affect significantly to economic growth in Indonesia as well as ZIS fund and the inflation simultaneously affected the economic growth significantly during 2011-2015 in Indonesia.